Evolution of the karyotype and sex chromosome systems in basal clades of araneomorph spiders (Araneae: Araneomorphae) - Král, Jirí; Musilová, Jana; St'áhlavský, Frantisek; Rezác, Milan; Akan, Zübeyde; Edwards, Robert L; Coyle, Frederick A; Almerje, Carles Ribera (Chromosome research, 2006)
Concepts of spider karyotype evolution are based mostly on advanced and most diversified clade, the entelegyne lineage of araneomorph spiders. Hence the typical spider karyotype is supposed to consist exclusively of acrocentric chromosomes including the multiple X chromosomes. However, our data show considerable diversity of chromosome morphology and sex chromosome systems in basal clades of araneomorphs. Karyotypes of basal araneomorphs consist of holocentric (superfamily Dysderoidea) or normal chromosomes with localized centromere. In males of basal araneomorphs the prophase of first meiotic division includes a long diffuse stage. Multiple X chromosomes are less common in basal clades. The sex chromosome system of many families includes a Y chromosome or nucleolus organizer region that occurs rarely in the entelegyne spiders. A derived X(1)X(2)Y system with an achiasmatic sex-chromosome pairing during meiosis was found in the families Drymusidae, Hypochilidae, Filistatidae, Sicariidae, and Pholcidae. This suggests a monophyletic origin of the families. In some lineages the X(1)X(2)Y system converted into an X0 system, as found in some pholcids, or into an XY system, which is typical for the family Diguetidae. The remarkable karyotype and sex chromosome system diversity allows us to distinguish four evolutionary lineages of basal araneomorphs and hypothesize about the ancestral karyotype of araneomorphs.
Keywords: Sex Chromosomes; Male; pohlavní chromozomy; chromozomy; karyotypizace; Metaphase; Karyotyping; Meiosis; biologická evoluce; mužské pohlaví; Spiders; meióza; Animals; ženské pohlaví; pavouci; Biological Evolution; Chromosomes; zvířata; metafáze; Female